ABILITYCORRECTIONAL INSTITUTIONS IN PREVENTING RECIDIVISM (STUDY AT CLASS IIA LANGKAT NARCOTICS PRISON) - Nur Muhammad Fadli Nasution; Hasdiana Juwita Bintang; Rahul Ardian Fikri (CV. RADJA PUBLIKA, 2025)
The strong correlation between crime and social interaction is implicitly reflected in the Criminal Code (KUH Pidana), which states that crime is essentially rooted in social interaction. And when that interaction causes harm to another party, a crime occurs. This is the premise that describes how the correlation between crime and social interaction is established. When a harmful act is regulated by criminal law, it is no longer categorized as merely a crime but becomes a criminal offense. This definition defines the act as behavior that, at a given time and within a given cultural context, is considered intolerable and must be corrected through the use of legal means. The author's background in formulating the problem in this research is:How is the capability of Correctional Institutions in Preventing Recidivism in Class IIA Langkat Narcotics Prison in an effort to prevent the phenomenon of repeated criminal acts? This research is a normative-empirical research with a live-case study category based on empirical observations of the implementation of provisions of correctional laws and regulations in Class II A Langkat Narcotics Prison to evaluate the effectiveness of the guidance of inmates in it related to efforts to prevent repeated criminal acts (recidive). He acknowledged that repeat offenders in the Class IIA Langkat Narcotics Prison experience annual recidivism. Therefore, he believes recidivism in his area is a common occurrence, as crime, which is a part of society, also accompanies crime. Where there is society, there is law; where there is law, there is crime; and where there is crime, there is recidivism. Therefore, the goal of rehabilitation is not to eliminate recidivism but to minimize it. To prevent character-based recidivism, the Class II A Langkat Narcotics Prison collaborates with Islamic, Christian, Hindu, and Buddhist religious leaders to provide regular spiritual guidance. This ensures that mental and spiritual development activities can benefit inmates.